2016
DOI: 10.15562/jdmfs.v1i1.142
|View full text |Cite
|
Sign up to set email alerts
|

Differences chronological age and dental age using Demirjian method based upon a study radiology using radiography panoramic at the Hasanuddin University Dental Hospital

Abstract: The aim of this literature review was to study the underlying mechanisms of the association between periodontal disease and prostate cancer. Methods: This study was literature review study, pubmed searching was used to find scientific article about association of periodontal disease and prostate cancer. Results: Direct correlation between periodontal disease and prostrate cancer is still unclear. It was hyphotesized that microorganisms involved in chronic periodontitis may directly induce mutations in the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Demirjian’s method has been the most widely used method and considered as the gold standard for dental age estimation 19 . Several literatures supports Demirjian’s method for dental age estimation in Northeastern Turkish children 20 , Malay population 21 , Western Chinese children 22 , Malaysian children 23 , Belgaum population 24 , Lucknow children 25 , Indian children 19 , and Indonesian children 26-28 .…”
Section: Introductionmentioning
confidence: 89%
“…Demirjian’s method has been the most widely used method and considered as the gold standard for dental age estimation 19 . Several literatures supports Demirjian’s method for dental age estimation in Northeastern Turkish children 20 , Malay population 21 , Western Chinese children 22 , Malaysian children 23 , Belgaum population 24 , Lucknow children 25 , Indian children 19 , and Indonesian children 26-28 .…”
Section: Introductionmentioning
confidence: 89%
“…There were 14 studies found from the conducted search, which summarized in Table 1. The age coverage of the most study was young adult and children (71%) [11][12][13][14][15][16][17][18][19][20] . Only three studies which involved age range more than 25 years [21][22][23] .…”
Section: Dental Age Estimation In Indonesian Populationmentioning
confidence: 99%
“…Only three studies which involved age range more than 25 years [21][22][23] . The youngest age of population involved in the studies was 4 years and the oldest was 73 years 11,22,23 . There is one study which did not specifically mentioned the age range information 24 .…”
Section: Dental Age Estimation In Indonesian Populationmentioning
confidence: 99%
See 1 more Smart Citation